PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI PADA KANTOR WILAYAH DIREKTORAT JENDERAL BEA DAN CUKAI (DJBC) RIAU DAN SUMATERA BARAT - Julianto, Romi Haryo; ', Susi Hendriani (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
The study was conducted at the Regional Office of Wilayah Direktorat Jenderal Bea Dan Cukai (DJBC) Riau and West Sumatra which is the government agencies that regulate and oversee the conduct of the field of export and import . The purpose of the study was to determine the effect of variable organizational culture and work motivation on job satisfaction , and then examine the effect of job satisfaction on performance . The study population were 58 people who constitute the total employees working in the Office of Wilayah Direktorat Jenderal Bea Dan Cukai (DJBC) Riau and West Sumatra . The variables used are the organizational culture and work motivation as an independent variable , job satisfaction as the dependent variable to be a mediating variable performance . The analytical tool used is the two stage least squares using SPSS 17 for windows . The results showed that the culture of the organization and motivational effect on employee job satisfaction . Furthermore , employee satisfaction affects employee performance.Kata Kunci : Organizational Culture , Work Motivation , Job Satisfaction and Employee Performance.